Theoretical aspects of determining the legal nature of delegation of powers in the system of local self-government of Ukraine - Vandyak , Anastasia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article analyzes and summarizes scientific approaches to interpreting the essence of the concept of "delegation of powers".Based on the theoretical analysis, it is determined that the presence of a special subject composition, which on the one hand is represented by the subject of delegation with the appropriate legal status, and on the other - by the executor of delegated powers, is a characteristic feature of the delegation of powers.Delegation as one of the methods of public administration is used by executive bodies to solve the problem of effective redistribution of powers between them. Its external management action is limited by the system of executive power and does not go beyond its limits. Only an authorized executive body, which is granted such a right by the Constitution of Ukraine and relevant laws, can transfer powers.The article, based on the analysis of theoretical principles, substantiates that delegation is most inherent in local government bodies, since public administration bodies themselves are created under such conditions when the community or community delegates power to them. As for local government bodies, the community delegates the right to exercise local self-government to certain public bodies - local councils, which, in turn, grant or delegate part of the powers to other bodies in the local government system.The use of delegation leads to the formulation of new tasks, among which the task of coordinating the activities of various links in the system of local government bodies acquires special importance. The feasibility and scope of delegation largely depend on the specific socio-economic and political situation, financial capabilities, and the nature of the tasks being solved.It was determined that more detailed legislative regulation of the institution of delegation of powers will help to competently distribute material resources and financial funds and achieve the goal of delegation of powers.The author draws conclusions, defines the concept of delegation of powers in the local government system, and identifies the characteristic features of delegation of powers in the local government system.